Analisis Perbandingan SAW, WP dan TOPSIS Untuk Rekomendasi Restoran - Sabandar, Vederico Pitsalitz; Wahyudi, Agung Deni (Jurnal Ilmiah Computer Science, 2024)
Choosing the right restaurant for your food is a decision that can affect your overall culinary experience. In this study, the data used is data from TripAdvisor in the form of ratings and ratings of restaurants in Lampung. The data taken is the top 5 ranking data in tripadvisor which will be an analysis in providing restaurant recommendations based on the rating data on the website. The ranking results using the SAW method Rank 1 was obtained by Square Restaurant with a final score of 0.895. The ranking results using the WP Rank 1 method were obtained by Square Restaurant with a final score of 0.203427. The ranking results using the TOPSIS method Rank 1 were obtained by Pempek 123 with a final value of 0.580511982. The results of a comparative analysis of SAW, WP, or TOPSIS depend on the complexity of the decision, user preferences, and the specific characteristics of the decision-making problem at hand. SAW lends itself to simple decision, WP provides greater flexibility on weight handling, and TOPSIS can provide more in-depth analysis by considering both positive and negative ideal matrices.